2008
DOI: 10.1002/ijc.23927
|View full text |Cite
|
Sign up to set email alerts
|

Space‐time clustering of childhood cancer around the residence at birth

Abstract: Previously, we identified space-time clustering in certain childhood cancers around diagnosis residence. These findings provided support for the involvement of environmental agents in etiological processes occurring close to diagnosis. We have reanalyzed the same British population-based dataset. The aim of the study was to determine whether there was space-time clustering around the residence at birth in relation to time of birth and separately from time of diagnosis. A total of 29,553 cases, diagnosed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 39 publications
2
34
0
1
Order By: Relevance
“…However, in the past decade, only a few studies that analyse the addresses during pregnancy, birth and diagnosis have emerged, showing more conclusive results with pregnancy and birth addresses. These studies support that development of childhood cancers initiates in utero or beginning of infancy, catalysed by a common exposure within a shared geographic area (Kreis et al, 2016; McNally et al, 2009b). Additionally, much progress has been made in the study of the geographical differences in areas with smaller populations, allowing the observation of major differences in low overall prevalence diseases like childhood AL (Ortega-Garcia et al, 2016).…”
Section: Introductionsupporting
confidence: 62%
“…However, in the past decade, only a few studies that analyse the addresses during pregnancy, birth and diagnosis have emerged, showing more conclusive results with pregnancy and birth addresses. These studies support that development of childhood cancers initiates in utero or beginning of infancy, catalysed by a common exposure within a shared geographic area (Kreis et al, 2016; McNally et al, 2009b). Additionally, much progress has been made in the study of the geographical differences in areas with smaller populations, allowing the observation of major differences in low overall prevalence diseases like childhood AL (Ortega-Garcia et al, 2016).…”
Section: Introductionsupporting
confidence: 62%
“…Although they cannot be directly compared, those studies found, as in our study, clusters within the large groups of total tumors, leukemias, tumors of the central nervous system, and lymphomas. 7,[24][25][26][27][28][29][30][31] However, those studies failed to establish a conclusive relationship between results and a socioenvironmental factor, even though the presence of clusters is probably an evidence of the fact that environmental factors are related to the presence and development of cancer. [32][33][34] Apart from ionizing radiation and some congenital genetic syndromes, there is little evidence -and lots of suspicion-regarding other factors that may influence the clustering of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien no pueden ser comparados de manera directa, estas investigaciones encuentran conglomerados, al igual que nosotros, dentro de los grandes grupos de tumores totales, leucemias, tumores del sistema nervioso central y linfomas. 7,[24][25][26][27][28][29][30][31] Sin embargo, estas investigaciones no pudieron, de manera concluyente, relacionar sus resultados con algún factor socioambiental, a pesar de que la presencia de los conglomerados probablemente sea evidencia de que los factores ambientales están relacionados con la presencia y desarrollo de la enfermedad. [32][33][34] Más allá de la radiación ionizante y algunos síndromes genéticos congénitos, existe poca evidencia, y muchas sospechas, de otros factores que tengan una influencia en el agrupamiento del cáncer pediátrico en conglomerados.…”
Section: Discussionunclassified